Histidine catabolism is a major determinant of methotrexate sensitivity - Kanarek, Naama; Keys, Heather R.; Cantor, Jason R.; Lewis, Caroline A.; Chan, Sze Ham; Kunchok, Tenzin; Abu-Remaileh, Monther; Freinkman, Elizaveta; Schweitzer, Lawrence D.; Sabatini, David M. (Nature (London), 2018)
The chemotherapeutic drug methotrexate inhibits the enzyme dihydrofolate reductase 1 , which generates tetrahydrofolate, an essential cofactor in nucleotide synthesis 2 . Depletion of tetrahydrofolate causes cell death by suppressing DNA and RNA production 3 . Although methotrexate is widely used as an anticancer agent and is the subject of over a thousand ongoing clinical trials 4 , its high toxicity often leads to the premature termination of its use, which reduces its potential efficacy 5 . To identify genes that modulate the response of cancer cells to methotrexate, we performed a CRISPR–Cas9-based screen 6 , 7 . This screen yielded FTCD , which encodes an enzyme—formimidoyltransferase cyclodeaminase—that is required for the catabolism of the amino acid histidine 8 , a process that has not previously been linked to methotrexate sensitivity. In cultured cancer cells, depletion of several genes in the histidine degradation pathway markedly decreased sensitivity to methotrexate. Mechanistically, histidine catabolism drains the cellular pool of tetrahydrofolate, which is particularly detrimental to methotrexate-treated cells. Moreover, expression of the rate-limiting enzyme in histidine catabolism is associated with methotrexate sensitivity in cancer cell lines and with survival rate in patients. In vivo dietary supplementation of histidine increased flux through the histidine degradation pathway and enhanced the sensitivity of leukaemia xenografts to methotrexate. The histidine degradation pathway markedly influences the sensitivity of cancer cells to methotrexate and may be exploited to improve methotrexate efficacy through a simple dietary intervention. Histidine metabolism influences the sensitivity of cancer cells to methotrexate, with mice bearing leukaemia xenografts showing increased response to the drug upon histidine supplementation.